Identifiability of single crystal plasticity parameters from residual topographies in Berkovich nanoindentation on FCC nickel. (May 2020) - Renner, E.; Bourceret, A.; Gaillard, Y.; Amiot, F.; Delobelle, P.; Richard, F.
Highlights: A method is built to quantify the information richness of Berkovich nanoindentation imprints at grain scale. An identifiability index is used to design a well-posed parameter identification problem from Berkovich residual topographies. Combining imprints, and especially pile-ups, improves the conditioning of the inverse problem. The interaction matrix of FCC structure seems identifiable using three topographies. Abstract: The information richness of imprints topographies obtained after Berkovich nanoindentation tests at grain scale is assessed for identifying all or part of the parameters of a single crystal plasticity law. In a previous paper (Renner et al., 2016), the strong potential of imprints topographies has been shown through a large experimental campaign conducted on nickel samples. A 3D crystal plasticity finite element modelling (CPFEM) of the nanoindentation experiment using the Méric-Cailletaud has also showed a large sensitivity of residual topographies to the indenter/grain orientation and to the plastic parameters, including the interaction matrix coefficients specifying the interactions between dislocations on different slip systems. This makes imprints topographies very good candidates to provide information for the single crystal parameters identification. The present paper focuses on the Méric-Cailletaud law parameters identifiability using residual topographies. A method is built to define the best well-posed inverse problem to ensure the parameters identification using a crystal plasticity finite element modelling updating (CPFEMU) method. An identifiability index proposed by Richard et al. (Richard et al., 2013) for measuring the information richness of the indentation curve is extended to the analysis of residual topographies. This index quantifies the possibility to achieve a stable/unstable solution using an inverse method. For the studied behaviour, the results show that eight of the nine Méric-Cailletaud law parameters can be identified using three topographies.